Investigation of Cycloparaphenylenes (CPPs) and their Noncovalent Ring‐in‐Ring and Fullerene‐in‐Ring Complexes by (Matrix‐Assisted) Laser Desorption/Ionization and Density Functional Theory. Issue 40 (1st July 2020) - Minameyer, Martin B.; Xu, Youzhi; Frühwald, Stefan; Görling, Andreas; von Delius, Max; Drewello, Thomas
Abstract: [ n ]Cycloparaphenylenes ([ n ]CPPs) with n =5, 8, 10 and 12 and their noncovalent ring‐in‐ring and [ m ]fullerene‐in‐ring complexes with m =60, 70 and 84 have been studied by direct and matrix‐assisted laser desorption ionization ((MA)LDI) and density‐functional theory (DFT). LDI is introduced as a straightforward approach for the sensitive analysis of CPPs, free from unwanted decomposition and without the need of a matrix. The ring‐in‐ring system of [[10]CPP⊃[5]CPP] +. was studied in positive‐ion MALDI. Fragmentation and DFT indicate that the positive charge is exclusively located on the inner ring, while in [[10]CPP⊃C60 ] +. it is located solely on the outer nanohoop. Positive‐ion MALDI is introduced as a new sensitive method for analysis of CPP⊃fullerene complexes, enabling the detection of novel complexes [[12]CPP⊃C60, 70 and 84 ] +. and [[10]CPP⊃C84 ] +. . Selective binding can be observed when mixing one fullerene with two CPPs or vice versa, reflecting ideal size requirements for efficient complex formation. Geometries, binding and fragmentation energies of CPP⊃fullerene complexes from DFT calculations explain the observed fragmentation behavior. Abstract : Cycloparaphenylenes and their complexes in the gas phase : A straightforward method—(MA)LDI—is introduced to characterize CPPs and their host–guest complexes either with another ring size or with different fullerenes. The method enables the detection of thus far unknown complexes. Fragmentation experiments and DFT calculations provide insight into geometries, binding and fragmentation energies as well as charge location of CPP host–guest complexes.